Age-dependent interaction of apolipoprotein E gene with eastern birthplace in Finland affects severity of coronary atherosclerosis and risk of fatal myocardial infarction—Helsinki Sudden Death Study. (May 2013) - Tyynelä, Petri; Goebeler, Sirkka; Ilveskoski, Erkki; Mikkelsson, Jussi; Perola, Markus; Lehtimäki, Terho; Karhunen, Pekka J.
<x xml:space="preserve">Abstract</x> Background. Mortality from coronary heart disease (CHD) has been constantly higher in eastern late settlement regions compared to western early settlements in Finland, unrelated to classical risk factors. In line with this, eastern birthplace was an age-dependent predictor of severe coronary atherosclerosis and pre-hospital sudden coronary death among male residents of Helsinki. We investigated a possible interaction of apolipoprotein E (APOE) gene with birthplace on the risk of myocardial infarction (MI) and coronary atherosclerosis. Method. APOE genotypes were analyzed in the Helsinki Sudden Death Study series comprising out-of-hospital deaths among males aged 33–70 years (n = 577), who were born in high (east, n = 273) or low (west, n = 304) CHD mortality area. Results. Eastern-born men ≤ 55 years carried 30% more often (P = 0.017) and older men 40% less often (P = 0.022) the APOE ϵ4 allele compared to western-born men (P = 0.003 for birthplace-by-age interaction). In multivariate analysis, the ϵ4 allele associated with the risk of out-of-hospital MI (odds ratio 2.58; 95% CI 1.20–5.55; P = 0.016) only in eastern-born men and with advanced atherosclerosis in both regions of origin, respectively. Conclusions. Birthplace-bound risk of CHD was age-dependently modified by APOE ϵ4 allele, suggesting genetic differences in CHD susceptibility between early and late settlement regions in Finland and providing one explanation for the eastern high mortality.